2017
DOI: 10.1037/hea0000436
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude uniquely predicts lower depression in chronic illness populations: A longitudinal study of inflammatory bowel disease and arthritis.

Abstract: Objective: Although gratitude has been identified as a key clinically relevant trait for improving well-being, it is understudied within medical populations. The current study addressed this gap and extended previous and limited cross-sectional research by examining the longitudinal associations of gratitude to depression in two chronic illness samples, arthritis and IBD. Results: At T2, 57.2 percent of the arthritis sample and 53.4 percent of the IBD sample met the cut off scores for significant depression. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 77 publications
4
76
0
1
Order By: Relevance
“…Gratitude uniquely contributes to both satisfaction with life and psychological well-being after controlling for both the domains and facets of the five-factor model of personality (Wood et al, 2008a;). Additionally, recent longitudinal studies on the associations of gratitude to psychological well-being in the context of chronic illness revealed that gratitude uniquely predicts lower depression six months apart (Sirois & Wood, 2017). Studies using cross-lagged panel design on healthy individuals also revealed similar results.…”
Section: Introductionsupporting
confidence: 63%
“…Gratitude uniquely contributes to both satisfaction with life and psychological well-being after controlling for both the domains and facets of the five-factor model of personality (Wood et al, 2008a;). Additionally, recent longitudinal studies on the associations of gratitude to psychological well-being in the context of chronic illness revealed that gratitude uniquely predicts lower depression six months apart (Sirois & Wood, 2017). Studies using cross-lagged panel design on healthy individuals also revealed similar results.…”
Section: Introductionsupporting
confidence: 63%
“…In line with the common approach of including baseline values as covariates to examine longitudinal change (Shankar & Hinds, in press; Sirois & Wood, 2017), we also examined the association between personality and changes in sleep quality in regression models with personality at baseline as a predictor of sleep at follow-up, including sleep at baseline and demographic variables as covariates. Baseline sleep medication and depressive symptoms were further controlled in supplemental analyses.…”
Section: Methodsmentioning
confidence: 99%
“…A growing evidence base indicates that gratitude, an orientation towards noticing and appreciating the positive in life [13], may be particularly beneficial for improving quality of life in clinical populations, including those with chronic health conditions. As a trait construct, gratitude is associated with lower levels of depression in those with heart failure and breast cancer [14,15], and longitudinally predicts lower depression in individuals with inflammatory bowel disease and arthritis [16]. Gratitude is also associated with enhanced quality of life in arthritis, chronic obstructive pulmonary disease, and diabetes [17], and better self-rated health, in people with inflammatory bowel disease and arthritis [16].…”
Section: Introductionmentioning
confidence: 99%
“…As a trait construct, gratitude is associated with lower levels of depression in those with heart failure and breast cancer [14,15], and longitudinally predicts lower depression in individuals with inflammatory bowel disease and arthritis [16]. Gratitude is also associated with enhanced quality of life in arthritis, chronic obstructive pulmonary disease, and diabetes [17], and better self-rated health, in people with inflammatory bowel disease and arthritis [16]. Yet to date, gratitude has not been specifically examined with respect to quality of life in FMS.…”
Section: Introductionmentioning
confidence: 99%